Efficacy and Tolerance of 5-Aminosalicylic Acid Suppositories in the Treatment of Ulcerative Proctitis: A Review of Two Double-Blind, Placebo Controlled Trials. (1st November 1990) - Williams, CN
Abstract : The efficacy and tolerance of 500 mg 5-aminosalicylic acid (mesalamine) suppositories in the treatment of ulcerative proctitis were assessed in two double-blind, placebo controlled studies of six weeks' duration, involving a total of 173 patients. In trial 1, patients used one 500 mg suppository tid. In trial 2, patients used one 500 mg suppository bid. Physician's global assessment and a disease activity index based upon patient symptoms and sigmoidoscopic appearance were used to assess efficacy. At the endpoint of trial l (tid), there was an 80.4% mean reduction in the disease activity index seen in patients treated with mesalamine compared to a 36.8% mean reduction in the placebo group (P<0.05). Analysis of the physician's global assessment indicated that 84.2% of patients receiving mesalamine were considered to be 'much improved' compared to 41 % of patients on placebo (P<0.01). At the endpoint of trial 2 (tid), there was a 74.7% mean reduction in disease activity index compared to 34.2% in the placebo group (P<0.001). Analysis of the physician's global assessment indicated that 79.2% of the mesalamine group was considered to be 'much improved' compared to 26.2% on placebo (P<0.001). There was no significant difference in efficacy seen in patients treated with 500 mg mesalamine suppositories bid or tid. Mesalamine suppositories are effective and well tolerated in the treatment of ulcerative proctitis.